ROLE OF COGNITIVE ENGAGEMENT ON ACADEMIC ACHIEVEMENT AT SECONDARY SCHOOL STUDENTS - Sarfraz Ahmed Khan,Irfan Haider (IJLTP, 2024)
The purpose of this research project was to investigate the role of cognitive engagement on academic accomplishment among students enrolled in secondary schools. The descriptive method was used in this investigation. The population of this study is made up of 29984 Matric students that are currently enrolled. The number 400 was chosen as the size of the sample after employing stratified random sampling. A researcher conceived of a self-rated questionnaire, which was then confirmed through pilot testing. The value of the instrument's Cronbach alpha coefficient came in at 0.911. The researcher went door-to-door, handed out questionnaires, and then personally collected their responses. The levels of academic achievement of students were determined based on the data kept at their respective schools. For the purpose of assessing the nature of the connection between cognitive engagement and academic success, the researcher relied on the Pearson r correlation coefficient. After doing the research, the researchers came to the conclusion that there was a substantial positive association between control and relevance, aspiration and future goals, and academic accomplishment. There was found to be no substantial correlation between academic success and motivation derived from outside sources. There was a substantial link between active cognitive participation and academic achievement in the aggregate.